Carbon Dioxide (CO2) laser cut quality of acrylic - Ahmad Shazwi, Kamaruzaman (2008)
This thesis presents the study of Acrylic were cut on CO2 laser cutting system and analyze the effects of power on cut quality. There are 2 cut quality involved during this thesis which are surface roughness and kerf width. Manual calculation analysis was used to investigate the effect of power on laser cut quality. The cutting process was implemented at apply power start from 15 – 28.5 W and 10 experiments were conduct during this thesis work. The feed rate will remain as constant variable parameter during this work study. Perthometer and image analyzer are conducted to examine the cut quality. From the analysis done, it was shown that the kerf width and surface roughness depends mainly on the laser power intensity. Power has great significance parameter in terms of improving productivity and good surface finish. As obtained through this thesis study, increasing the power intensity resulted in smaller value of surface roughness, Ra and higher value of kerf width.